Fingerprint watermarking with tamper localization and exact recovery using multi-level authentication - Wei, Keat Lee; Liew, Siau-Chuin (Penerbit UMP, 2018)
This paper presents the tamper localization and exact recovery using multi-level authentication in fingerprint watermarking. The proposed scheme will be detecting the tampered sector of fingerprint images when the watermark is embedded in the original image. If the sector has been tampered, the sector will be able to recover the original data. Furthermore, exact pixel value of the fingerprint image is used to embed the feature of extraction and recovery of the original fingerprint image from the tampered image. This paper also describes the usage of SHA-256 as a hash function, the usage of Least Significant Bit (LSB) technique to perform tamper detection, localization and recovery in the Region of Interest (ROI). The proposed scheme does not require original fingerprint for detection on the tampered sector and recovery. It uses 512 x 512 pixels fingerprint images and 288 x 180 pixels of ROI in this study. The experimental results showed that the tamper detection and localization were successfully detected and localized the tampered sector. The tampered sectors were restored accurately and the average peak signal-to-noise ratio (PSNR) value of watermarked image was 44.1518 dB. The experimental result proved the effectiveness of multi-level authentication.